A major increase in winter snowfall during the middle Holocene on western Greenland caused by reduced sea ice in Baffin Bay and the Labrador Sea - Thomas, Elizabeth K.; Briner, Jason P.; Ryan-Henry, John J.; Huang, Yongsong (Geophysical Research Letters, 2016)
Recent observations indicate that ice-ocean interaction drives much of the recent increase in mass loss from the Greenland Ice Sheet; however, the role of ocean forcing in driving past glacier change is poorly understood. To extend the observational record and our understanding of the ocean-cryosphere link, we used a multi-proxy approach that combines new data from proglacial lake sediments, C-14-dated in situ moss that recently emerged from beneath cold-based ice caps, and Be-10 ages to reconstruct centennial-scale records of mountain glacier activity for the past similar to 10 k. y. in West Greenland. Proglacial lake sediment records and C-14 dating of moss indicate the onset of Neoglaciation in West Greenland at ca. 5 ka with substantial snowline lowering and glacier expansion at ca. 3.7 ka followed by additional ice expansion phases at ca. 2.9, ca. 1.7, and ca. 1.4 ka and during the Little Ice Age. We find that widespread glacier growth at ca. 3.7 ka in West Greenland coincides with marked cooling and reduced strength of the West Greenland Current in Disko Bugt. The transition to cooler ocean conditions at ca. 3.7 ka identified in Disko Bugt is registered by marine proxy data farther afield in East Greenland and on the northwestern Icelandic shelf, implying large-scale paleoceanographic changes across the North Atlantic during this interval. The similarity between glacier change on West Greenland and multiple marine and terrestrial records across the North Atlantic suggests that glaciers are strongly influenced by changes in ocean circulation and consequently implies that the ocean-cryosphere teleconnection is a persistent feature of the Arctic system.